DEVELOPMENT OF FADN IN SERBIA, MONTENEGRO AND BOSNIA AND HERZEGOVINA (EU CANDIDATE COUNTRIES) AND THE TRANSITION TOWARDS FSDN - Nastić, Lana; Todorović, Saša; Ivanović, Sanjin; Očić, Vesna (Economics of Agriculture, 2026)
All the candidate countries for the European Unionaccession are obliged to establish Farm AccountancyData Network as a way of recording and analyzing farmactivities, agricultural policy creation and monitoring.Observed countries (Serbia, Montenegro and Bosnia andHerzegovina) are in different phases of establishing thatsystem. The goal of the research was to discuss levelof development of Farm Accountancy Data Networkin observed countries and readiness of transition toFarm Sustainability Data Network. To achieve that goalqualitative comparative analysis was used. The resultsindicated the highest level of development in Serbia, whileBosnia and Herzegovina is still at the beginning of theprocess. Farm Accountancy Data Network developmentin Montenegro could be estimated as medium. Itwas concluded that observed countries face certainchallenges when it comes to transformation of existingsystem towards broader concept of sustainability. All thecountries should work on capacity-building strategies,particularly in Montenegro and Bosnia and Herzegovina,to provide successful transition to system which is moresustainability-oriented.